2020
DOI: 10.1039/d0fo01072c
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of oolong tea extracts against glutamate-induced toxicity in cultured neuronal cells and β-amyloid-induced toxicity inCaenorhabditis elegans

Abstract: The schematic of neuroprotective effects of oolong tea extracts against glutamate-induced toxicity in cultured neuronal cells and Aβ/α-synuclein-induced toxicity in Caenorhabditis elegans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…We suggested that the optimal concentration of AO extract is need for antioxidant and protective properties (Supplementary Material Figure S4). The neuroprotective effects of AO extracts are consistent with antioxidant properties against neurotoxicity of anacardic acids (Salehi et al, 2019), gallic acid (Oiram Filho et al, 2018), catechin (Herges et al, 2011;Zhang et al, 2020) and quercetin (Yang et al, 2014;Khan et al, 2018;Park et al, 2019).…”
Section: Involvement Of Signaling Pathway In Anacardium Occidentale L Extracts Induced Neurite Outgrowth In Neuro-2a Cellssupporting
confidence: 61%
See 2 more Smart Citations
“…We suggested that the optimal concentration of AO extract is need for antioxidant and protective properties (Supplementary Material Figure S4). The neuroprotective effects of AO extracts are consistent with antioxidant properties against neurotoxicity of anacardic acids (Salehi et al, 2019), gallic acid (Oiram Filho et al, 2018), catechin (Herges et al, 2011;Zhang et al, 2020) and quercetin (Yang et al, 2014;Khan et al, 2018;Park et al, 2019).…”
Section: Involvement Of Signaling Pathway In Anacardium Occidentale L Extracts Induced Neurite Outgrowth In Neuro-2a Cellssupporting
confidence: 61%
“…For Teneurin-4 (Ten-4) knockdown, On-Target Plus small interfering RNA (siRNA), which contains the targeting sequence of Ten-4 (Thermo Fisher Scientific), was used. Specific siRNAs of the Ten-4 gene were designed according to Suzuki et al (2014) , Zhang et al (2020) (sense: 5′- GAU​UGU​GGC​AAA​CUA​GUA​U-3′, antisense: 5′- AUA​CUA​GUU​UGC​CAC​AAU​C-3′). Transfection of Neuro-2a cells was accomplished using Lipofectamine ® 2000 (Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These extracts also increased the average neurite length and induced the expression of GAP-43 and Ten-4 involved in neural development in Neuro-2a cells. Moreover, they had protective effects against Aβ-induced paralysis, chemotaxis deficiency, and α-synuclein aggregation in C. elegans [ 141 ]. Teaghrelin, a compound in oolong tea, activated AMP-activated protein kinase (AMPK)/sirtuin 1(SIRT1)/peroxisome proliferator-activated receptor gamma (PPARγ) coactivator-1α (PGC-1α) and extracellular signal-regulated kinases 1 and 2 (ERK1/2) pathways in SH-SY5Y cells to antagonize mitochondrial toxin, MPP + -induced cell death [ 142 ].…”
Section: Herbal Teas and Autophagymentioning
confidence: 99%
“…For Teneurin-4 (Ten-4) knockdown, On-Target Plus small interfering RNA (siRNA), which contains the targeting sequence of Ten-4 (Thermo Fisher Scientific), was used. Specific siRNAs of the Ten-4 gene were designed according to Suzuki et al (2014), Zhang et al (2020) (sense: 5′-GAUUGUGGCAAACUA GUAU-3′, antisense: 5′-AUACUAGUUUGCCACAAUC-3′). Transfection of Neuro-2a cells was accomplished using Lipofectamine ® 2000 (Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Knockdown Of Teneurin-4 Expressionmentioning
confidence: 99%